AB1014 Enlarging the Clinical Spectrum of Sting-Associated Vasculopathy with Onset in Infancy (SAVI). (9th June 2015) - Caorsi, R.; Rice, G.; Cardinale, F.; Volpi, S.; Buoncompagni, A.; Crow, Y.; Martini, A.; Gattorno, M.; Picco, P.
Abstract : Background: SAVI syndrome is a recently identified condition associated to mutations of TMEM173. Up to know only few cases of this disease have been described. Objectives: To describe the clinical manifestation of an Italian patient affected by SAVI syndrome Results: The girl, first born from healthy, not relatives parents, at the age of 8 months started to present erythematosus-infiltrated skin lesions with pustular evolution and finally hesitating in scars in 15-20 days. From the age of three years chilblains and severe nail dystrophy appeared. At the age of 8 years the girl presented a severe pneumonia, requiring prolonged antibiotic therapy. The chest CT performed showed, in addition to the lung infiltrate, the presence of diffuse interstitial thickening with ground-glass appearance. A restrictive framework was detected at spirometry (FVC 51%). The autoantibodies detection revealed positive ANA (1: 160), ANCA (1:80) and Coombs test; rheumatoid factor was slightly increased. Anti-DNA and ENA were negative. The skin biopsy revealed a predominantly granulomatous nodular dermatitis, with aspects of deep granulomatous folliculitis and secondary fibrosis. The lung biopsy revealed focal hemorrhage, edema and predominantly lymphocytic inflammatory aggregates in the peribronchial interstitial areas with aspects of capillaritis and contiguous focal subatelettasia with alveolar cavity filled of macrophages. In the following months, in light of the progression of the disease, steroidal treatment (prednisone 1 mg/kg/day) was started with improvement of clinical manifestation, anemia and normalization of inflammatory markers. However attempts to reduce such therapy were followed by an exacerbation of the clinical picture. In the attempt to reduce steroidal treatment, the child was treated wit both immunosuppressive (azathioprine) and biologic (etanercept) drugs, without clear improvement. Unsatisfactory growth was also detected. In the following months the child started to present a mild renal involvement with microscopic hematuria and hypertension, requiring anti-hypertensive treatment. Given the evocative framework, interferon gene signature was performed, revealing a significant activation; the molecular analysis of TMEM173 gene showed the presence of the de novo Val155Met mutation, already described as causative of SAVI syndrome. The child continued to present persistent severe microcytic anemia, requiring erythrocytes' transfusions, despite high levels of erythropoietin. Bone marrow aspiration was therefore performed, that revealed dysmaturative signs in the in erythroid progenitors. Conclusions: This report of the first Italian patient with SAVI syndrome confirms the presence of the previously described clinical manifestations. Persistent hematuria and hypertension are reasonably signs of an underlying renal involvement, not previously described in this condition. Thus a renal biopsy is needed for confirmation. The origin of severe anemia is still unclear. Thus a possible deregulatory effect of mutated STING protein on bone marrow progenitors has to be investigated and is actually under study in our patient. Disclosure of Interest: None declared